The Role of Brand Love in Mediating the Influence of Brand Trust on Consumer Loyalty of Sariayu Cosmetics - Baiq Asya Faras Khairunnisa; Muhammad Mujahid Dakwah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Background: The Indonesian cosmetics industry faces intense competition, with Sariayu experiencing declining market share from 15% in 2020 to 8.9% in 2024, indicating weakened consumer loyalty. Purpose: This study examines the mediating role of brand love in the relationship between brand trust and consumer loyalty toward Sariayu facial mask products. Methods: A quantitative explanatory design was employed with purposive sampling of 150 University of Mataram students aged 18-25 years with minimum twice product usage. A five-point Likert scale questionnaire was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Brand trust significantly influenced brand love (β = 0.785, p < 0.001). Both brand trust (β = 0.661, p < 0.001) and brand love (β = 0.230, p = 0.009) positively affected consumer loyalty. Brand love partially mediated the trust-loyalty relationship, indicating emotional bonds amplify trust effects on loyalty. Conclusion: Brand love functions as a significant mediator between brand trust and consumer loyalty, emphasizing the importance of cultivating both cognitive trust and affective commitment in building sustainable loyalty for local cosmetic brands. These findings validate theoretical frameworks while extending applicability to the Indonesian halal cosmetics industry.